Static Crow’s Feet Treated with Voltaic Arc Dermabrasion (Atmospheric Plasma): Post-Operative Pain Assessment by Thermal Infrared Imaging - Scarano, Antonio (J Clin Med, 2021)
Background: In the literature, several strategies have been described for the treatment of unaesthetic marks on the face resulting from the aging processes. The atmospheric plasma procedure is a non-invasive, inexpensive technique proposed for the rejuvenation of facial tissues. The aim of this study was to evaluate the performance of voltaic arc dermabrasion (VAD) for the treatment of static crow’s feet of the periorbital area. Methods: The crow’s feet of 135 patients (127 female and 8 male) were treated using the VAD technique. The perioperative skin temperature measurement was assessed using an Infrared Temperature sensor. The pain was measured using the Visual Analogic Score (VAS) at 1 week, 1 month and 1 year. The patient’s and surgeon’s satisfaction were assessed using the Global Aesthetic Improvement Scale (GAIS) at 1 month and 1 year from the procedure. The severity of the crow’s feet was rated using the Crow’s Feet Grading Scale (CFGS). Results: A complete epidermal healing of all the subjects treated was evident at 7 days. The atmospheric plasma technique showed an efficient treatment for the removal of the crow’s feet, with a good aesthetic outcome, high surgeon and patient satisfaction, without clinical complications. Conclusions: The atmospheric plasma technique can be a useful modality in the cosmetic as well as therapeutic treatment of crow’s feet.